Assessing Nursing Students' Knowledge of Genomic Concepts and Readiness for Use in Practice. Issue 2 (March 2016) - Munroe, Theresa; Loerzel, Victoria
Abstract : Nurses are expected to apply genomic concepts in clinical practice. This study evaluated undergraduate nursing students' genomic knowledge and attitudes about using this knowledge in practice. Using a pretest-posttest design, findings indicated that students' knowledge was poor, but improved over a semester with genomics content. Most students did not feel ready to use this knowledge in the clinical setting. These findings suggest the need for more genomic education in nursing curriculum.